Republication of "Ultrasonographic Appearance of Lung Sliding in a Patient With a Bronchopleural Fistula on a High-Frequency Oscillator Ventilator". (July 2020) - Wallace, David John; Sappington, Penny; Tisherman, Samuel; Stone, Michael
The patient with a bronchopleural fistula and acute respiratory distress syndrome can present a therapeutic challenge for the treating clinician. In this case, the authors describe the use of bedside thoracic sonography to show real-time improvement in a pneumothorax after initiation of high-frequency oscillatory ventilation. Sonography may have a role in the evaluation of ventilator strategies in the future, although validation of this application is still needed.